Factors Affecting the U.S Supreme Court’s Reversal of Its Constitutional Precedents - عباس قصي علي; الشويلي حسين جبر حسين (Journal of Legal Sciences, 2021)
• S. Supreme Court plays a very important rule in American legal system, especially in the domain of constitutional interpretation and judicial review. This importance emerges from the precedents of the court which considered as compulsory rules on all the authorities. However, the supreme court can overrule its precedents. This research is about the factors which effect the court’s decision on overruling, dividing them on internal and external factors. The source of the internal factors is the precedent itself, while the source of the external factors is the circumstances surrounding the precedent.